Annealed microstructure dependent corrosion behavior of Ti-6Al-3Nb-2Zr-1Mo alloy. (30th January 2021) - Su, Baoxian; Luo, Liangshun; Wang, Binbin; Su, Yanqing; Wang, Liang; Ritchie, Robert O.; Guo, Enyu; Li, Ting; Yang, Huimin; Huang, Haiguang; Guo, Jingjie; Fu, Hengzhi
Abstract: Corrosion resistance of titanium (Ti) alloys is closely connected with their microstructure which can be adjusted and controlled via different annealing schemes. Herein, we systematically investigate the specific effects of annealing on the corrosion performance of Ti-6Al-3Nb-2Zr-1Mo (Ti80) alloy in 3.5 wt.% NaCl and 5 M HCl solutions, respectively, based on open circuit potential (OCP), potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), static immersion tests and surface analysis. Results indicate that increasing annealing temperature endows Ti80 alloy with a higher volume fraction of β phase and finer α phase, which in turn improves its corrosion resistance. Surface characterization demonstrates that β phase is more resistant to corrosion than α phase owing to a higher content of Nb, Mo, and Zr in the former; additionally, the decreased thickness of α phase alleviates segregation of elements to further restrain the micro-galvanic couple effects between α and β phases. Meanwhile, the influential mechanisms of environmental conditions on corrosion of Ti80 alloy are discussed in detail. As the formation of a highly compact and stable oxide film on surface, annealed Ti80 alloys exhibit a low corrosion current density (10 −6 A/cm 2 ) and high polarization impedance (10 6 Ω⋅ cm 2 ) in 3.5 wt.% NaCl solution. However, they suffer severe corrosion in 5 M HCl solution, resulting from the breakdown of native oxide films (the conversion of TiO2 to aqueous Ti 3+ ), active dissolution of substrate Ti to aqueous Ti 3+ and existence of micro-galvanic couple effects. Those findings could provide new insights to designing Ti alloys with high-corrosion resistance through microstructural optimization.